The systemic implications of bail-in: a multi-layered network approach - Anne-Caroline Hüser; Grzegorz Hałaj; Christoffer Kok; Cristian Perales; Anton van der Kraaij (European Central Bank (ECB), 2017)
We present a tractable framework to assess the systemic implications of bail-in. To this end, we construct a multi-layered network model where each layer represents the securities cross holdings of a specific seniority among the largest euro area banking groups. On this basis, the bail-in of a bank can be simulated to identify the direct contagion risk to the other banks in the network. We find that there is no direct contagion to creditor banks. Spill-overs also tend to be small due to low levels of securities cross-holdings in the interbank network. We also quantify the impact of a bail-in on the different liability holders. In the baseline scenario, shareholders and subordinated creditors are always affected by the bail-in, senior unsecured creditors in 75% of the cases. Finally, we compute the effect of the bail-in on the network topology in each layer. We find that a bail-in significantly reshapes interbank linkages within specific seniority layers.
Keywords: G01; G18; G21; C63; 330; bail-in; financial networks; policy simulation; resolution regimes; systemic risk